Analisis Pengaruh Waktu Latensi Terhadap Akurasi Sistem SCADA Bacaan Metering Listrik Waktu Nyata Melalui Jaringan Internet - Endra Joelianto; Fuady Ramdhani; Eko Mursito Budi (Universitas Syiah Kuala, 2020)
SCADA (Supervisory Control and Data Acquisition) system of electricity metering using the internet network aims to monitor electrical energy remotely by utilizing internet services. The system consists of a meter that measures electric quantities acquired by a server located close to the meter. The client reads data acquired by the server through the internet network. The use of internet networks for data transmission generally results in latency time, which affects the validity of the data read by the client, resulting in reduced cumulative power calculation accuracy. In this article, energy calculations using current, voltage and power factor data on the client are compared with the energy value calculated by the power meter. Errors that occur are used to calculate the accuracy of the system. The experiment resulted in latency times ranging from 110 ms - 11219 ms with an average of 572.3025 ms with valid data ranging from 93% of population data and accuracy values ranging from 99.2974% to 99.8648%. The resulting accuracy is within the ANSI C12.20 standard.